Digital Ethics: Social Media Ethics in a Contemporary Islamic Perspective - Rozanatush Shodiqoh (Solo International Collaboration and Publication of Social Sciences and Humanities, 2024)
In today's digital era, social media has become an integral part of daily life, including for Muslims around the world. However, uncontrolled use of social media can lead to various ethical problems. This research aims to explore the ethics of social media in a contemporary Islamic perspective, with a focus on ethical principles directed by Islamic teachings in interacting and communicating on digital platforms. The study adopts a qualitative approach, analyzing primary and secondary sources related to ethics in Islam and its application in the context of social media. The results of the study show that ethical principles in Islam, such as honesty, courtesy, and responsibility, are very relevant and can be applied to the use of social media. The study found that while social media offers a variety of benefits, such as da'wah and religious learning, its users must remain vigilant against negative potentials such as slander, ghibah (gossip), and the spread of false information. The study proposes several practical recommendations for the ethical use of social media according to Islam, including an emphasis on Islamic digital education, the development of Sharia-based social media policies by social media platforms, and the formation of positive online communities.